Los seis errores más comunes en la interpretación jurídica ecuatoriana - César Coronel Jones (Universidad Hemisferios, 2008)
The main purpose of this work is to correct the misconception prevailing in culture of the Ecuadorian legal interpretation of the law. For this, the author through constructive criticism, stated six misconceptions quite accepted by our lawyers, judges and public officials. Also develops an introductory study on the purpose of the interpretation of the law and its associated elements.